Comparing student and faculty perceptions on the instructional value of iPads in art and design education - Souleles, Nicos; Watters, Hilary; Annesley, Angela; Savva, Stefania (My University, 2014)
This paper compares the perceptions of art and design students and faculty of the instructional value of iPads. More specifically, this paper draws from the main conclusions of two previous studies to compare the views of the two stakeholders, using as a framework of comparison the Rieber and Welliver (1995) five-step hierarchical model of technology adoption. Briefly, in the two previous studies both students and faculty were given the freedom to use iPads for teaching and learning, but without a specific task to guide their use. This bottom-up approach was deliberate, and together with the characteristics of art and design education and in particular the dominant modes of teaching and learning, provide the delimitations of the earlier studies. When comparing – in this paper – the outcomes of the previous two studies we noted that the adoption pattern was restricted mostly to the first two stages of the Rieber and Welliver (1995) model, familiarisation and utilization, with some effort from faculty to integrate iPads in curricula. We argue that integration, reorientation and evolution – the latter stages of the model - require change that can only be achieved if all stakeholders share in the process.
Keywords: Art and design education; Students; Faculty; iPads; Models of technology adoption